Intervention for First Graders With Limited Number Knowledge: Large-Scale Replication of a Randomized Controlled Trial. (June 2015) - Gersten, Russell; Rolfhus, Eric; Clarke, Ben; Decker, Lauren E.; Wilkins, Chuck; Dimino, Joseph
Replication studies are extremely rare in education. This randomized controlled trial (RCT) is a scale-up replication of Fuchs et al., which in a sample of 139 found a statistically significant positive impact for Number Rockets, a small-group intervention for at-risk first graders that focused on building understanding of number operations. The study was relatively small scale (one site) and highly controlled. This replication was implemented at a much larger scale—in 76 schools in four urban districts; 994 at-risk students participated. Intervention students participated in approximately 30 hours of small-group work in addition to classroom instruction; control students received typical instruction and whatever assistance the teacher would normally provide. Intervention students showed significantly superior performance on a broad measure of mathematics proficiency.